Intensification For Swiddening Community: Does Sawah Farming System Affect Traditional Customs and Values? - Markus Markus (Sekolah Pascasarjana Universitas Brawijaya, 2020)
The objective of this study was to describe the impacts of intensification on the indigenous community in West Kalimantan, using the Dayak Desa community in Ensaid Panjang as a case study. The resilience-vulnerability concept was utilized in analyzing the decline of swiddens in which a value-based approach to vulnerability and adaptation necessitates an analysis of values affected. The findings suggest that swidden agriculture is no longer integral but supplemental to local community livelihood where a more permanent way of cultivating is getting more prevalent. Along with this shift is the demise of some value-laden rituals and practices traditionally associated with shifting cultivation. The findings reinforce widely held views that global economic change and government‘s policy interventions have dramatically impacted the livelihood of the indigenous communities to the point where traditions and cultural values are at stake.